Isolation of regulators of Drosophila immune defense genes by a double interaction screen in yeast. - Junell, A.; Uvell, H.; Pick, L.; Engstrom, Y. (Insect Biochemistry and Molecular Biology, 2007)
Innate immunity is a universal and ancient defense system in metazoans against microorganisms. Antimicrobial peptides, which are synthesized both in insects and humans, constitute an endogenous, gene-encoded defense arsenal. In Drosophila, antimicrobial peptides, such as the potent cecropins, are expressed both constitutively in barrier epithelia, as well as systemically in response to infection. Rel/NF-kappaB proteins are well-known regulators of antimicrobial peptide genes, but very few Rel/NF-kappaB co-factors and/or tissue-specific regulators have been identified. We performed a double interaction screen in yeast to isolate Drosophila cDNAs coding for direct regulators, as well as Dif co-regulators, of the CecropinA1 gene. Three classes of positive cDNA clones corresponding to 15 Drosophila genes were isolated and further characterized. One of the Dif-independent cDNAs encoded the Rel/NF-kappaB protein Relish; a well-known activator of antimicrobial peptide genes in Drosophila, demonstrating the applicability of this type of screen for isolating regulators of immune defense. Most interestingly, three transcription factors belonging to the POU domain class of homeodomain proteins, Pdm1, Pdm2 and Dfr/Vvl were isolated as Dif-interacting partners, and subsequently verified as regulators of CecA1 expression in Drosophila cells. The importance of POU proteins in development and differentiation in Drosophila and mammals is well documented, but their role in regulation of Drosophila immune defense genes is a new and essential finding.